Global Occurrence and Chemical Impact of Stratospheric Blue Jets Modeled With WACCM4. Issue 5 (12th March 2019) - Pérez‐Invernón, F. J.; Gordillo‐Vázquez, F. J.; Smith, A. K.; Arnone, E.; Winkler, H.
Abstract: In this work we present the first parameterizations of the global occurrence rate and chemical influence of Blue Jets, a type of transient luminous event taking place in the stratospheric region above thunderclouds. These parameterizations are directly coupled with five different lightning parameterizations implemented in the Whole Atmosphere Community Climate Model (WACCM4). We have obtained a maximum Blue Jet global occurrence rate of about 0.9 BJ per minute. The geographical occurrence of Blue Jets is closely related to the chosen lightning parameterization. Some previously developed local chemical models of Blue Jets predicted an important influence onto the stratospheric concentration of N2 O, NO x, and O3 . We have used these results together with our global implementations of Blue Jets in WACCM4 to estimate their global chemical influence in the atmosphere. According to our results, Blue Jets can inject about 3.8 Tg N2 O‐N/year and 0.07 Tg NO‐N/year near the stratosphere, where N2 O‐N and NO‐N stand for the mass of nitrogen atoms in N2 O and NO molecules, respectively. These production rates of N2 O and NO x could have a direct impact on, for example, the acidity of rainwater or the greenhouse effect. We have found that Blue Jets could also slightly contribute to the depletion of stratospheric ozone. In particular, we have estimated that the maximum difference in the concentration of O3 at 30 km of altitude between simulations with and without Blue Jets can be about −5% in equatorial and polar regions. Plain Language Summary: Blue Jets are upward propagating conical‐shaped electrical discharges reaching 40 km of altitude. Blue Jets are triggered as a consequence of the electrical breakdown produced between the storm upper charge layer and the screening charge attracted to the cloud top. According to local chemical models of Blue Jets, they can inject a significant amount of nitric oxide (NO) and nitrous oxide (N2 O) into the atmosphere, causing a decrease in the local density of ozone (O3 ). This predicted local chemical influence of Blue Jets suggests a nonnegligible role of Blue Jets in the global atmospheric chemistry. In this work we present the first parameterization of the global occurrence rate and chemical influence of Blue Jets. We implement this parameterization in the Whole Atmosphere Community Climate Model to predict the global influence of Blue Jets in the atmosphere. According to our results, Blue Jets could inject into the atmosphere about 3.8 Tg N2 O‐N and 0.07 Tg NO‐N/year. According to our results, these chemical species could contribute to a slight depletion of stratospheric ozone about 5%. Key Points: The first parameterizations of the global occurrence rate and chemical influence of Blue Jets are presented The estimated global occurrence rate of Blue Jets is reproduced in a general circulation model Blue Jets can have a nonnegligible influence in the global concentrations of nitric oxide, nitrous oxide, ozone, and other chemical species